Alfabetización informacional en estudiantes de la carrera profesional de educación inicial facultad de ciencias de la educación y humanidades UNAP, Iquitos 2022 - Melendez Ramirez, Karen Minola (2024)
The purpose of the study was to determine the level of knowledge about information literacy in early education students at the UNAP Faculty of Education. It had a sample population of 192 students, to whom a questionnaire was applied. A basic descriptive research was carried out with a quantitative approach and nonexperimental and transversal design. It was determined that the majority, 62.5%, presented a medium level of knowledge of information literacy. In relation to the dimensions, it was identified that the majority, 50.6%, of the students demonstrate a medium level of information search, while 48 .4% show a high level in this skill. Regarding the selection of information, concentration is observed in 60.4%, who have a high level, followed by 37.5% who show a medium level in this task. Regarding the organization of information, 50% of the students are at a medium level, followed by 47.9% who have a high level in this aspect. Regarding the evaluation, the majority, 55.7% of the students, are at a medium level, while 42.7% present a high level. In conclusion, the students who participated in the research present a medium level of knowledge of information literacy.